Pelatihan Kewirausahaan Pada Masa Pandemi COVID-19 Dengan Memanfaatkan Media Digital Bagi Para Remaja Lingkungan RT 04, Bambu Apus, Pamulang, Kota Tangerang Selatan - Citra Eliyani; Syarifah Ida Farida; Dana Dana; Budi Syamtoro; Ratnawati Ratnawati (Lembaga Kajian Demokrasi dan Pemberdayaan Masyarakat (LKD-PM), 2021)
This community service is titled training to be an entrepreneurship in the Pandemic COVID-19 by digital media at RT 04 Bambu Apus, Pamulang, South Tangerang City. The purpose of this community service activity is to provide entrepreneurs training during COVID-19 pandemic by utilizing digital media to teenagers. The methods used are survey methods and direct material delivery, social service as well as simulations and discussions with teenagers of RT 04 Bambu Apus. The resulted of this activity is that participants received direct training to become entrepreneurs by digital media, such as: they can make their own shops in an e- commerce and be able to make product photography by utilizing materials around which are no longer used.